Metformin Treatment: A Potential Cause of Megaloblastic Anemia in Patients with Type 2 Diabetes Mellitus - Albai O (Dove Medical Press, 2020)
Oana Albai,1,2 Bogdan Timar,2,3 Diana Loreta Paun,4 Alexandra Sima,1,2 Deiana Roman,1,2 Romulus Timar1,2 1Second Department of Internal Medicine, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 2Department of Diabetes and Metabolic Diseases, “Pius Brinzeu” Emergency Hospital, Timisoara, Romania; 3Department of Functional Sciences, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 4Department of Public Health, Associate Professor in the Department of Endocrinology, “Carol Davila” University of Medicine and Pharmacy, Bucuresti, RomaniaCorrespondence: Bogdan Timar“Victor Babes“ University of Medicine and Pharmacy, 2 Eftimie Murgu, Timisoara 300041, RomaniaTel +40741528093Email timar.bogdan@umft.roIntroduction: Vitamin B12 (cobalamin) deficiency is a frequent cause of megaloblastic anemia, manifested through various symptoms. Screening for this deficiency can be justified in case of patients with one or more risk factors present from the following: gastric resections, inflammatory bowel disease, use of metformin over a prolonged period of time, administration of proton pump inhibitors or H2 histamine receptor blockers for more than 12 months and in case of adults over 75 years of age. One method of determining vitamin B12 deficiency is measuring its serum levels, as well as performing measurements of serum levels of methylmalonic acid and homocysteine levels, which experience an increase in the early stages of vitamin B12 deficiency.Clinical Case: We bring to your attention, the case of a 62 years old patient diagnosed with Type 2 Diabetes Mellitus in 2015 that presented in the emergency room in October 2019 with an altered general condition, nausea, vomiting, abdominal pain, palpitation, and dyspnea. Treatment with metformin was initiated from the diagnosis of Type 2 Diabetes Mellitus, four years before. Investigations established the diagnosis of megaloblastic anemia by vitamin B12 deficiency. The symptoms disappeared after the injection of vitamin B12.Conclusion: Periodical dosing of vitamin B12 should be performed in the case of patients with Type 2 Diabetes Mellitus treated with metformin, especially if they associate anemia and/or peripheral diabetic polyneuropathy.Keywords: megaloblastic anemia, metformin, vitamin B12 deficiency